Reformulation of the Education System: Negotiating the Gap in Access to Education Through Strengthening Social Capital Capacity - Sapulette, Alce Albartin; Ritiauw, Benico (Journal of Social Science and Business Studies, 2025)
The development of the education system in the 3T region has always been a never-ending discourse. Suboptimal development progress, limited access to basic infrastructure, and acute disparities that impact the quality of community education make the 3T region interesting to discuss in order to formulate various functional approaches to the community and regional context, as seen in Abio and Huku Kecil. Using qualitative research methods, this research prioritizes a community-based perspective as an option to formulate an adaptive and functional education system to the objective conditions of the community, by formulating social capital as a basic framework for developing an inclusive and bottom-up education system as an effort to reform the characteristics of the education system that tends to be top-down and direct rules. This research found that the activation of a community-based social approach that includes bonding social capital, bridging social capital, and linking social capital, functions to bridge various strategic educational needs through the active involvement of community members as networked subjects and forming a support system in the implementation of education. The span of regional control that hinders the redistribution of educational resources, without realizing it, frames the creative efforts of the community in overcoming the complexities inherent in itself.